A Role Financial Inclusion in Moderating Digital Literacy, Innovation, and Certification for SMEs - Cahyo, Septian Dwi; Mubarok, Ahmad Shofi; Astuti, Fitria Yuni (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study examines the moderating role of financial inclusion in the relationship between digital literacy, innovation, and certification in maintaining the sustainability of SMEs in Kendal Regency. A quantitative approach was used, with a sample of 210 SMEs operators in Kendal Regency who have been in operation for more than one year, possess business licenses, and hold product certifications. The findings indicate that digital literacy and certification positively influence SMEs sustainability. However, innovation did not show a positive effect on SMEs' sustainability. Furthermore, financial inclusion was found not to moderate the relationship between digital literacy and innovation concerning SMEs sustainability, but it did strengthen the relationship between certification and SMEs sustainability.